Toward a criminology of the Holocaust?: a historical overview of "states of denial" to foster a criminological analysis of the crime of the century = Auf dem Weg zu einer Kriminologie des Holocausts? : ein historischer Überblick über "Zustände der Verleugnung" als Grundlage für eine kriminologische Analyse - Vegh Weis, Valeria (Kriminologisches Journal, 2023)
Despite its still marginal position, state crime criminology has contributed to a criminological agenda that specifically deals with harms perpetrated by states and other powerful actors. Nevertheless, many relevant areas and topics within state crime research remain unexplored, including the study of the “crime of the century”. Indeed, although the Holocaust is often invoked as the paradigmatic case of state crime, little has been produced on the subject by criminologists – an urgent, unresolved task. This article aims at fostering this pending undertaking by engaging with a core notion developed within criminological studies: states of denial (Cohen 2001). This concept is deployed to analyse not only the period where crimes were committed but also the long-durée aftermath in Germany. Concerning the aftermath and based on Olick’s periodization (2013), the study particularly explores the role of the Allies and the (Western) Federal Chancellors in dealing with the atrocities of the past. Altogether, this contribution, which builds upon the few criminological approaches to the study of the Holocaust (Friedrichs 2000; Karstedt 2010; Morrison 2013), is presented as a limited attempt towards the development of a “Criminology of the Shoah”. Such a criminology cannot only help overcome certain criminological myopia about a breaking point in the history of atrocity crimes but can also help set a strong basis for a broader criminological understanding of atrocities and the massive suffering and challenges that stemmed from them throughout time.